Development and characterization of the superconducting integrated receiver channel of the TELIS atmospheric sounder - de Lange, G.; Birk, Manfred; Boersma, D.; Dercksen, J.; Dmitriev, P.; Ermakov, A.B.; Filippenko, L.V.; Golstein, H.; Hoogeveen, R.; de Jong, L.; Khudchenko, A.; Kinev, N.; et al. (Superconductor Science and Technology, 2010)
The balloon-borne instrument TELIS (TErahertz and submillimetre LImb Sounder) is a three-channel superconducting heterodyne spectrometer for atmospheric research use. It detects spectral emission lines of stratospheric trace gases that have their rotational transitions at THz frequencies. One of the channels is based on the superconducting integrated receiver (SIR) technology. We demonstrate for the first time the capabilities of the SIR technology for heterodyne spectroscopy in general, and atmospheric limb sounding in particular. We also show that the application of SIR technology is not limited to laboratory environments, but that it is well suited for remote operation under harsh environmental conditions. Within a SIR the main components needed for a superconducting heterodyne receiver such as a superconductorÃ¢ÂÂinsulatorÃ¢ÂÂsuperconductor (SIS) mixer with a quasi-optical antenna, a flux-flow oscillator (FFO) as the local oscillator, and a harmonic mixer to phase lock the FFO are integrated on a single chip. Light weight and low power consumption combined with broadband operation and nearly quantum limited sensitivity make the SIR a perfect candidate for use in future airborne and space-borne missions. The noise temperature of the SIR was measured to be as low as 120 K, with an intermediate frequency band of 4Ã¢ÂÂ8 GHz in double-sideband operation. The spectral resolution is well below 1 MHz, confirmed by our measurements. Remote control of the SIR under flight conditions has been demonstrated in a successful balloon flight in Kiruna, Sweden. The sensor and instrument design are presented, as well as the preliminary science results from the first flight.